Bays, Beaches, and Bioethical Barkings - Solbakk, Jan Helge (Cambridge quarterly of healthcare ethics, 2011)
From my flat on the eighth floor, I enjoy the panoramic view of the bay and beaches of Montevideo. Except for days of rain and stormy weather—which happen often in these months of winter—the beach is frequented by dogs and their masters and mistresses. I have a passion for dogs, and every morning and afternoon I take short breaks to watch from my window the playfulness of my four-feeted soulmates. They differ in race, color, and size, but from a bird’s-eye view, these differences are negligible, as are the differences in their behavior: they all stop to sniff and deposit their “biological fingerprints” at exactly the same places, they leap and jump around, they move back and forward in different directions, always close to water—a few of them even risk brief visits into the water—and always ahead of their guardians, though not too far away from them. Only occasionally do I observe barking confrontations. Often, however, I see them joined in ceremonial acts aimed at repeatedly outshining each other with regard to “depositional” pace and outreach.